Six years of activity of the Italian vaccine portal “VaccinarSì”: a web traffic evaluation using Google Analytics - Bordin, P.; Melot, B.; Tralli, V.; Bertoni, C.; Moretti, F.; Siddu, A.; Baldo, V.; Bonanni, P.; Castiglia, P.; Majori, S.; Ferro, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Despite the scientific consensus about vaccines safety and effectiveness, there is still a discrepancy between scientific evidence and perception by the general population. The “VaccinarSì” portal was created in 2013 by Italian specialists in Public Health to provide evidence-based information regarding vaccination.Study Design. The purpose of this study was to analyse the web traffic on “VaccinarSì” platform during a six-year period (May 8, 2013-May 8, 2019). Moreover, we compared the first six-month with the last sixmonth period of the website activity, to identify potential areas of improvements.Methods. This is a descriptive study using Google Analytics data. We collected data regarding the following: total number of sessions to the portal, total number of pages viewed, total number of users and the number of new visitors, geographical locations and demography of users as well as user access mode (type of device used and way of access). We also collected some data that were informative about the possibility to infer the level of visitors’ engagement with the portal, such as thee number of returning users, bounce rate, number of pages visited per session and mean session duration.Results. Throughout the relevant period, the portal has consistently increased its popularity, with a remarkable increment of monthly connections (ending up to more than 80,000/month) from all over Italy. Visitors were mainly female (71.1%), aged between 25 and 44 years (64.7%). Healthcare professionals were responsible for a considerable proportion of accesses (50.6%). The mobile has become the dominant device used to access the portal, accounting for 77.8% of total connection in the last six months. Similarly, in the last period, organic search accounted for 92% of all connections. Measles and MPR vaccine, as well as chickenpox and hexavalent vaccine, have remained the most appealing topics of interest among visitors over the years. The page that attracted more visitors over the six years was “real risks and benefits of vaccination”, accounting for 5.67% of total sessions with a high mean duration spent of 05:08 minutes. Conclusions. During the six years of activity, overall, the level of users’ engagement with the portal has dropped with an increased bounce rate and a lower average number of pages visited per session and a lower mean duration of each connection. The lowest engagement involved connections accessed through mobile devices. Results helped “Vaccinarsi” developers to speculate about future strategies to further increase the platform popularity and optimize visitors’ engagement.